2020
DOI: 10.1101/2020.07.07.191965
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The developing relations between networks of cortical myelin and neurophysiological connectivity

Abstract: AbstractRecent work identified that patterns of distributed brain regions sharing similar myeloarchitecture are related to underlying functional connectivity, demonstrating cortical myelin’s plasticity to changes in functional demand. However, the changing relation between functional connectivity and structural architecture throughout child and adulthood is poorly understood. We show that structural covariance connectivity measured using T1-weighted/T2-weighted ratio and functi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Patients with PTSD were shown to have alterations in neural activity and functional connectivity of the SMG as compared to healthy controls ( Bastos et al, 2022 ; Dossi et al, 2020 ; Felmingham et al, 2009 ; Rabellino et al, 2018 ). In addition, preliminary evidence has suggested that the associations of ICM with cognitive function may be through its importance for the integrity of neural connections and neural synchrony of cerebral cortex, particularly the facilitation of local brain synchrony ( Grydeland et al, 2016 ; Vandewouw et al, 2021 ; Yang et al, 2020 ). Demyelination has been considered as a biomarker for some neurological diseases such as multiple sclerosis ( Lucchinetti et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PTSD were shown to have alterations in neural activity and functional connectivity of the SMG as compared to healthy controls ( Bastos et al, 2022 ; Dossi et al, 2020 ; Felmingham et al, 2009 ; Rabellino et al, 2018 ). In addition, preliminary evidence has suggested that the associations of ICM with cognitive function may be through its importance for the integrity of neural connections and neural synchrony of cerebral cortex, particularly the facilitation of local brain synchrony ( Grydeland et al, 2016 ; Vandewouw et al, 2021 ; Yang et al, 2020 ). Demyelination has been considered as a biomarker for some neurological diseases such as multiple sclerosis ( Lucchinetti et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, structure-function relationships in brain connectivity are notoriously complex. 69,70 To disentangle these alternatives, we analyzed paired diffusion data of the cingulum and uncinate tracts from a subset of patients. Bayesian analysis provided an initial test due to limitations of the small sample 71 and suggested that age-related differences in both coupling mechanisms reflect maturation of the cingulum.…”
Section: Discussionmentioning
confidence: 99%
“…Graph theoretical measures have been increasingly used in an effort to accurately represent structural and functional dependence among brain regions 24,25 . Previous studies have shown that structural covariance networks derived from cortical myelin values align to a significant extent with functional connectivity networks 26,27 . Several studies have observed significant structural network changes in other brain disorders such as schizophrenia/psychosis, 28,29 obsessive‐compulsive disorder, 30 mild traumatic brain injury, 31 Parkinson's disease, 32 Alzheimer's disease 33 and binge drinking 34 .…”
Section: Introductionmentioning
confidence: 99%